X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x^9y^9
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 19:36:41
X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x^9y^9X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x^9y^9X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x
X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x^9y^9
X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x^9y^9
X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x^9y^9
3+m+n=9
m-1+2n+2=9
解方程组,得m=4 , n=2
(Y-X)^3*(X-Y)^m+(X-Y) ^m+1*(Y-X)^2
计算:(1).(2x-3y)/(y-x)-(x+2y)/(x-y) (2).[5m/(m-3)+2m/(m+3)]*(m^2-9)/m
分解因式x^m+3-2x^m+2y+x^m+1y^2
分解因式:x^m+3-2x^m+2*y+x^m+1*y^2
分解因式x^m+3-(2x^m+2)y+(x^m+1)y^2
(x-2y)^m+1/(x-2y)^m-3/(2y-x)^3怎么算
计算:2/1-m-1/m-1.2x/x-y -y/y-x -y-2x/x-y.12/m²-9 -2/m-3
3(x-1)³y-(1-x)³z m(x-y)²-x+y x²(x+y)(y-x)-xy(x+y)(x-y) 因式分解
计算:(y-x)^3(x-y)^m-(x-y)^m+2(y-x)
4m(x-y)-2m^2(y-x)^3
(x-y)m次方(y-x)2m次方+(y-x)3m次方得几
计算(x-y)^m(y-x)^2m+(y-x)^3m
已知x>y,m
X^3*y^(m-1)*x^(m+y)*y^(2n+2)=x^9y^9
因式分解:2x^5m-1 * y^m -4x^3m-1 * y^m+2 +2x^m-1 * y^n+4
计算题:9(x-y)^3[-1/9(x-y)^m+5](y-x)^2
若多项式5x*x-2mxy-3y*y+4xy-3x+1中不含xy项,求(-(m*m*m)+2(m*m)-m+1)-(m*m*m+2m*m-m+4)
已知方程组3x+2y=m+1,2x+y=m-1,当m为何值时,x>y且2x<3y?